Taxonomic revision of the genus Benthana Budde-Lund, 1908 (Isopoda: Oniscidea: Philosciidae) - Campos-Filho, Ivanklin Soares; Taiti, Stefano; Araujo, Paula Beatriz (Zootaxa, 2015)
The neotropical genus Benthana (Philosciidae) is reviewed. Fourteen species are redescribed: Benthana picta, B. olfersii, B. longicornis, B. schubarti, B. albomarginata, B. werneri, B. santosi, B. longipenis, B. bocainensis, B. moreirai, B. dimorpha, B. iporangensis, B. sulcata, and B. longicaudata. Additional characters were proposed for B. convexa, B. taeniata, B. serrana, B. trinodulata, B. araucariana, and B. cairensis. New records are provided for 13 species, and four new species are described: Benthana aimores sp. nov., Benthana goitacas sp. nov., Benthana tupinamba sp. nov. and Benthana canastraensis sp. nov.. Two Chilean species are considered incertae sedis. A pictorial key and distribution maps for the species are provided.